Analisis Kadar Abu Biochar Tongkol Jagung Dengan Pupuk NPK Menggunakan Metode Coating - Ngguna, Adriana Kaita; Iskandar , Taufik; Abrina Anggraini , Sinar Perbawani (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
Indonesia is a country with large population growth. The increasing number of occupations resulted in an increased need for food. One of the efforts made to meet these needs is by increasing agricultural yields such as fertilization and farming to maintain soil fertility to obtain optimal agricultural yields. The use of corn cobs and NPK biochar has an adverse effect on plants due to changes in pH in the soil, and about 20-70% of fertilizers are degraded or washed away by groundwater, so fertilization is ineffective and efficient and will pollute the environment with N content, P and K. This study aims to analyze the ash content of corn cobs biochar with NPK fertilizer using the coating method. The coating is a process for coating material by wrapping, soaking, or spraying it to provide resistance to the material and provide protection against the material. The raw material used is corn cobs biochar. The variables determined were a mixture of biochar and NPK fertilizer: 10%, 20%, and 30% with starch concentrations of 10%, 20%, and 30%. The results of the analysis obtained the lowest ash content value with the composition of biochar and NPK with a concentration of 10% coated with starch with a 30% concentration of 0.0557%. While the highest ash content was in the concentration of biochar and NPK with a concentration of 30% with a concentration of 10% starch at 0.1353%.